George Ramos [Journalism 1969] - George Ramos::::::::: (1984)
Republished in Cal Poly Today Summer 1984, page 8. Photo caption reads: "Pulitzer Prize Winner ... Journalism graduate George Ramos helped the Los Angeles Times win the Pulitzer gold medal for meritorious public service. Ramos was co-editor of a series on the Latino community that was hailed as a landmark by the Pulitzer board." Article by Ginny Monteen, no photo credit given.